К вопросу о некоторых жанровых особенностях анекдотического текста - Герасимчик, А.О.; Татарникова, И.В. (Культура народов Причерноморья, 2014)
Статья выполнена в русле исследований, посвященных изучению специфики
взаимодействия текстового, жанрового и дискурсивного аспектов анекдота, и описывает жанровую
природу англоязычных анекдотических текстов и их стилистические особенности. Данная тема
исследования является весьма актуальной, поскольку позволяет выявить универсальные инвариантные
особенности анекдота в рамках игрового дискурса. В статье представлены классификации анекдотов с
учетом их структуры и тематической принадлежности, а также обосновывается необходимость
более глубокого анализа особенностей вербальной экспликации социальных стереотипов гендерной
концептосферы в английских анекдотах. В качестве экспериментального материала были использованы
сборники английских анекдотов “English Humour”, а также другие интернет-ресурсы. Стаття виконана у руслі досліджень, присвячених вивченню специфіки взаємодії
текстового, жанрового та дискурсивного аспектів анекдоту, та описує жанрову природу англомовних
анекдотичних текстів та їх стилістичні властивості. Ця тема дослідження є вельми актуальною,
оскільки дозволяє виявити універсальні інваріантні особливості анекдоту у межах жартівливого
дискурсу. У статті надані класифікації анекдотів з урахуванням їх структури та тематичної
приналежності, а також обгрунтовується необхідність більш глибокого аналізу особливостей
вербальної експлікації соціальних стереотипів гендерної концептосфери в англійських анекдотах. У
якості експериментального матеріалу було використано збірники англійських анекдотів " English
Humour”, а також інтернет-ресурси. The article matches investigations dedicated to the study of the interrelation of the textual, genre and
discourse aspects of an anecdote, and describes the genre nature of English anecdotic texts and their stylistic
peculiarities. The present theme appears to be rather topical because it indicates the domain within which it is
possible to extract certain universal invariant features of an anecdote representing an integral component of the
humorous discourse. The article also presents an overview of theories elaborated by scholars concerning the
definition of an anecdote and an extensive description of various classifications of anecdotes which are based on
such criteria as the compositional structure of an anecdote and its thematic reference. Among the results are
motivational arguments testifying to the necessity of the particularizing study of the relevant peculiarities of the verbal manifestation of the social stereotypes and social expectations forming the gender conceptual sphere in
English anecdotes. Anecdotic texts of this kind can be defined as social and their preliminary analysis shows that
in the majority of cases they display some particular aspects of discrimination by gender. The object of genderbiased
ridicule is usually presented through one or two nuclear gender-specific features and several marginal
distinctions which according to the national cultural tradition and relevant social expectations correlate with the
concept of male and female gender. Such social gender-related anecdotes tend to have satirical content
permeated with elements of irony and sarcasm. Their subsequent analysis with the application of axiological
evaluation markers can yield additional data particularizing relevant features of gender concept in English
culture. Collections of English anecdotes “English Humour” and other online Internet resources have been used
as a source of experimental material.